“Persistent ecological impacts related to West Nile virus revealed using community science and vector surveillance data” - Brock Geary; Adam C. Smith; Lisa Williams; Sean P. Murphy; Brandon P.M. Edwards; Nicole L. Michel; Timothy D. Meehan; Roderick B. Gagne (Biological Conservation, 2026)

Parasites as conservation tools - Roderick B. Gagne; Kevin R. Crooks; Meggan E. Craft; Elliott S. Chiu; Nicholas M. Fountain‐Jones; Jennifer L. Malmberg; Scott Carver; W. Chris Funk; Sue VandeWoude (Conservation Biology, 2022)
Parasite success typically depends on a close relationship with one or more hosts; therefore, attributes of parasitic infection have the potential to provide indirect details of host natural history and are biologically relevant to animal conservation. Characterization of parasite infections has been useful in delineating host populations and has served as a proxy for assessment of environmental quality. In other cases, the utility of parasites is just being explored, for example, as indicators of host connectivity. Innovative studies of parasite biology can provide information to manage major conservation threats by using parasite assemblage, prevalence, or genetic data to provide insights into the host. Overexploitation, habitat loss and fragmentation, invasive species, and climate change are major threats to animal conservation, and all of these can be informed by parasites.

Translocations maintain genetic diversity and increase connectivity in sea otters, Enhydra lutris - Shawn Larson; Roderick B. Gagne; Jim Bodkin; Michael J. Murray; Katherine Ralls; Lizabeth Bowen; Raphael Leblois; Sylvain Piry; Maria Cecilia Penedo; M. Tim Tinker; Holly B. Ernest (Marine Mammal Science, 2021)
Sea otters, Enhydra lutris , were once abundant along the nearshore areas of the North Pacific. The international maritime fur trade that ended in 1911 left 13 small remnant populations with low genetic diversity. Subsequent translocations into previously occupied habitat resulted in several reintroduced populations along the coast of North America. We sampled sea otters between 2008 and 2011 throughout much of their current range and used 19 nuclear microsatellite markers to evaluate genetic diversity, population structure, and connectivity between remnant and reintroduced populations. Average genetic diversity within populations was similar: observed heterozygosity 0.55 and 0.53, expected heterozygosity 0.56 and 0.52, unbiased expected heterozygosity 0.57 and 0.52, for reintroduced and remnant populations, respectively. Sea otter population structure was greatest between the Northern and Southern sea otters with further structuring in Northern sea otters into Western, Central, and Southeast populations (including the reintroduced populations). Migrant analyses suggest the successful reintroductions and growth of remnant groups have enhanced connectivity and gene flow between populations throughout many of the sampled Northern populations. We recommend that future management actions for the Southern sea otter focus on future reintroductions to fill the gap between the California and Washington populations ultimately restoring gene flow to the isolated California population.

A natural laboratory to elucidate the evolution of endogenous‐exogenous retroviral interactions - Elliott S. Chiu; Roderick B. Gagne (Molecular Ecology, 2021)
The advent of whole genome sequencing has revealed much about the genomes of animals including the relatively large percentage of the genome consisting of endogenous retroviruses (ERV; International Human Genome Sequencing Consortium, 2001). An ERV arises when a retrovirus integrates into a host germ cell genome through normal infection processes. Germline infections can be transmitted to offspring through Mendelian inheritance and at times become fixed elements of the host genome (Weiss, 2006). At their inception, these endogenized retroviruses maintain all the functions of their exogenous progenitors and can produce infectious virus (Figure 1). Mutations in the ERV randomly accumulate over time and can lead to the loss of the deleterious effects. In addition, the ERV can provide benefits to the host often via limiting exogenous viral infections (Chiu and VandeWoude, 2020a). However, most of these endogenous viruses are evolutionary relics representing historical infections and have no contemporary exogenous virus. This limits the opportunities to understand the evolution of ERVs and their interactions with exogenous viruses. In this issue of Molecular Ecology , Quigley et al. (2020) use a novel approach to show that koala retrovirus (KoRV) is undergoing endogenization along a geographic gradient with a variety of exogenous variants dispersed across the landscape. This system provides an opportunity to further elucidate the complex mechanisms in which endogenous and exogenous viruses interact and follow the evolution of an ERV in real time.

Correction to: Novel hybrid finds a peri-urban niche: Allen’s Hummingbirds in southern California - Braden L. Godwin; Melanie E. F. LaCava; Beth Mendelsohn; Roderick B. Gagne; Kyle D. Gustafson; Sierra M. Love Stowell; Andrew Engilis; Lisa A. Tell; Holly B. Ernest (Conservation Genetics, 2020)

Novel hybrid finds a peri-urban niche: Allen’s Hummingbirds in southern California - Braden L. Godwin; Melanie E. F. LaCava; Beth Mendelsohn; Roderick B. Gagne; Kyle D. Gustafson; Sierra M. Love Stowell; Andrew Engilis; Lisa A. Tell; Holly B. Ernest (Conservation Genetics, 2020)

Population genomic diversity and structure at the discontinuous southern range of the Great Gray Owl in North America - Beth Mendelsohn; Bryan Bedrosian; Sierra M. Love Stowell; Roderick B. Gagne; Melanie E. F. LaCava; Braden L. Godwin; Joshua M. Hull; Holly B. Ernest (Conservation Genetics, 2020)

Urbanization reduces genetic connectivity in bobcats ( Lynx rufus ) at both intra– and interpopulation spatial scales - Christopher P. Kozakiewicz; Christopher P. Burridge; W. Chris Funk; Patricia E. Salerno; Daryl R. Trumbo; Roderick B. Gagne; Erin E. Boydston; Robert N. Fisher; Lisa M. Lyren; Megan K. Jennings; Seth P. D. Riley; Laurel E. K. Serieys; et al. (Molecular Ecology, 2019)
Urbanization is a major factor driving habitat fragmentation and connectivity loss in wildlife. However, the impacts of urbanization on connectivity can vary among species and even populations due to differences in local landscape characteristics, and our ability to detect these relationships may depend on the spatial scale at which they are measured. Bobcats ( Lynx rufus ) are relatively sensitive to urbanization and the status of bobcat populations is an important indicator of connectivity in urban coastal southern California. We genotyped 271 bobcats at 13,520 SNP loci to conduct a replicated landscape resistance analysis in five genetically distinct populations. We tested urban and natural factors potentially influencing individual connectivity in each population separately, as well as study–wide. Overall, landscape genomic effects were most frequently detected at the study–wide spatial scale, with urban land cover (measured as impervious surface) having negative effects and topographic roughness having positive effects on gene flow. The negative effect of urban land cover on connectivity was also evident when populations were analyzed separately despite varying substantially in spatial area and the proportion of urban development, confirming a pervasive impact of urbanization largely independent of spatial scale. The effect of urban development was strongest in one population where stream habitat had been lost to development, suggesting that riparian corridors may help mitigate reduced connectivity in urbanizing areas. Our results demonstrate the importance of replicating landscape genetic analyses across populations and considering how landscape genetic effects may vary with spatial scale and local landscape structure.

Urbanization impacts apex predator gene flow but not genetic diversity across an urban‐rural divide - Daryl R. Trumbo; Patricia E. Salerno; Kenneth A. Logan; Mathew W. Alldredge; Roderick B. Gagne; Christopher P. Kozakiewicz; Simona Kraberger; Nicholas M. Fountain‐Jones; Meggan E. Craft; Scott Carver; Holly B. Ernest; Kevin R. Crooks; et al. (Molecular Ecology, 2019)
Apex predators are important indicators of intact natural ecosystems. They are also sensitive to urbanization because they require broad home ranges and extensive contiguous habitat to support their prey base. Pumas ( Puma concolor ) can persist near human developed areas, but urbanization may be detrimental to their movement ecology, population structure, and genetic diversity. To investigate potential effects of urbanization in population connectivity of pumas, we performed a landscape genomics study of 130 pumas on the rural Western Slope and more urbanized Front Range of Colorado, USA. Over 12,000 single nucleotide polymorphisms (SNPs) were genotyped using double‐digest, restriction site‐associated DNA sequencing (ddRADseq). We investigated patterns of gene flow and genetic diversity, and tested for correlations between key landscape variables and genetic distance to assess the effects of urbanization and other landscape factors on gene flow. Levels of genetic diversity were similar for the Western Slope and Front Range, but effective population sizes were smaller, genetic distances were higher, and there was more admixture in the more urbanized Front Range. Forest cover was strongly positively associated with puma gene flow on the Western Slope, while impervious surfaces restricted gene flow and more open, natural habitats enhanced gene flow on the Front Range. Landscape genomic analyses revealed differences in puma movement and gene flow patterns in rural versus urban settings. Our results highlight the utility of dense, genome‐scale markers to document subtle impacts of urbanization on a wide‐ranging carnivore living near a large urban center.

Genetic source–sink dynamics among naturally structured and anthropogenically fragmented puma populations - Kyle D. Gustafson; Roderick B. Gagne; T. Winston Vickers; Seth P. D. Riley; Christopher C. Wilmers; Vernon C. Bleich; Becky M. Pierce; Marc Kenyon; Tracy L. Drazenovich; Jeff A. Sikich; Walter M. Boyce; Holly B. Ernest (Conservation Genetics, 2019)

Phylogeography of the widespread creek chub Semotilus atromaculatus (Cypriniformes: Leuciscidae) - Susana Schönhuth; Roderick B. Gagne; Fernando Alda; David A. Neely; Richard L. Mayden; Michael J. Blum (Journal of Fish Biology, 2018)
The extent and nature of genetic differentiation in Semotilus atromaculatus , one of the most abundant and widespread leuciscids in North America, were evaluated based on mitochondrial (mt) and nuclear DNA sequence variation. Phylogenetic relationships were first inferred based on a fragment of the cytochrome b ( cytb ) region and the nuclear intron s7 gene for S. atromaculatus and all other congeners as well as representative species from all other genera in the creek chub–plagopterin clade. The phylogeography of major haplogroups of S. atromaculatus was also assessed according to variation in a fragment of the mitochondrial cytb region from 567 individuals across its range. All analyses identified S. thoreauianus , S. lumbee and S. corporalis as reciprocally monophyletic groups. Analyses of nuclear sequence variation resolved S. atromaculatus as a single clade, where S. thoreauianus and S. lumbee were recovered as the sister group to S. atromaculatus , and S. corporalis was resolved as sister to all other species in the genus. Analyses of mtDNA sequence variation recovered S. atromaculatus as three well supported and differentiated monophyletic groups, with a widespread genetically homogeneous lineage extending across most of the current range of the species; a more geographically restricted and geographically structured lineage in the southern Appalachians, sister group to S. lumbee ; and a geographically restricted lineage was identified from two Gulf Slope basins. Evidence of complex mito‐nuclear discordance and phylogeographic differentiation within S. atromaculatus illustrates that further analysis of widespread species is warranted to understand North American freshwater fish diversity and distributions.

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)